The use of Helmholtz resonators and panel absorbers in the design of duct silencers - A. TROCHIDIS; G. PAPANIKOLAOU (Archives of Acoustics)
The use of Helmholtz resonators and panel absorbers in reducing the noise propagated in ducts is investigated both analytically and experimentally. Using a simple approach, the impedance of the resonators is calculated taking into account the presence of sound absorbing material in the cavity. Equations for the transmission loss are derived in both cases. Parameters such as dimensions, length of the opening and flow resistivity of the lining in case of Helmholtz resonators and panel thickness and dimensions in case of panel absorbers are systematically examined. Comparisons between experimental and predicted values are in good agreement showing that the model developed describes satisfactorily the behaviour of resonators in ducts and can be used for improved design of silencers incorporating resonators.